FIRST BRAZILIAN CONSENSUS ON MULTIMODAL TREATMENT OF COLORECTAL LIVER METASTASES. MODULE 1: PRE-TREATMENT EVALUATION - COIMBRA,Felipe José Fernandez (2015)
Background : Liver metastases of colorectal cancer are frequent and potentially fatal event in the evolution of patients with these tumors. Aim : In this module, was contextualized the clinical situations and parameterized epidemiological data and results of the various treatment modalities established. Method: Was realized deep discussion on detecting and staging metastatic colorectal cancer, as well as employment of imaging methods in the evaluation of response to instituted systemic therapy. Results : The next step was based on the definition of which patients would have their metastases considered resectable and how to expand the amount of patients elegible for modalities with curative intent. Conclusion : Were presented clinical, pathological and molecular prognostic factors, validated to be taken into account in clinical practice.